The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/cncr.31983
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of surveillance imaging in patients with head and neck cancer who are treated with definitive radiotherapy

Abstract: Background The current study was performed to assess the efficacy of surveillance imaging in patients with head and neck cancer (HNC) who are treated definitively with radiotherapy. Methods Eligible patients included those with a demonstrable disease‐free interval (≥1 follow‐up imaging procedure without evidence of disease and a subsequent visit/imaging procedure) who underwent treatment of HNC from 2000 through 2010. Results A total of 1508 patients were included. The median overall survival was 99 months, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…8,15,30 Schwartz et al 15 reported that 86% of recurrent disease was detected clinically, and no survival benefit was found in those who had the disease detected by imaging alone. This model provides a potential framework to establish a more cost-effective and time-effective surveillance program.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…8,15,30 Schwartz et al 15 reported that 86% of recurrent disease was detected clinically, and no survival benefit was found in those who had the disease detected by imaging alone. This model provides a potential framework to establish a more cost-effective and time-effective surveillance program.…”
Section: Discussionmentioning
confidence: 99%
“…8 Although the data used in this model were Cancer February 15, 2020 based on a single-institution data set, they included follow-up data on >1500 patients with a median follow-up of 99 months-allowing the model to make assumptions as "real-life" as possible. 8 Although the data used in this model were Cancer February 15, 2020 based on a single-institution data set, they included follow-up data on >1500 patients with a median follow-up of 99 months-allowing the model to make assumptions as "real-life" as possible.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations